Portfolio Choice in the Presence of Housing - Cocco, João F. (Review of Financial Studies, 2005)
I show that investment in housing plays a crucial role in explaining the patterns of cross-sectional variation in the composition of wealth and the level of stockholdings observed in portfolio composition data. Due to investment in housing, younger and poorer investors have limited financial wealth to invest in stocks, which reduces the benefits of equity market participation. House price risk crowds out stockholdings, and this crowding out effect is larger for low financial net-worth. In the model as in the data leverage is positively correlated with stockholdings.